Allergenic extracts from Metarhizium anisopliae: Obtainment and characterization - Barbieri, Regina Teixeira; Croce, J.; Gandra, R. F.; Gagete, E. [UNESP]; Paula, C. R.; Gambale, W. (My University, 2005)
Metarhizium anisopliae is used as a biopesticide for insects that damage agricultural plantations like sugar cane and forage plants. In a previous study the sensitization to this fungus of asthmatic patients coming from sugar cane areas was showed. The aims of this work were: to compare crude extracts obtained with Tris-HCl and Coca liquid from several growth phases of M. anisopliae concerning the total content of proteins and their electrophoretic analysis profile; to evaluate in vivo allergic sensitization in Balb/c mice and allergic patients from a sugar cane area, and to characterize the allergenic fractions in the sera of patients positive for the prick test by means of Western-blotting. The extract obtained with Coca liquid on the 16th day was the one that presented the greatest number of proteic fractions, including all those present in the other extracts. Twelve fractions were verified in this extract with approximate molecular weights from 94 to 14 kDa. The allergenicity of the extract obtained on the 16th day was proven by the production of IgE antibodies in Balb/c mice, with titres of 200. Prick tests carried out with the extract of the 16th day in 79 atopic individuals (from sugar cane area), 35 atopic individuals (from urban area) and 11 non- atopic individuals showed respective positivity of 29%, 9% and 0%. The allergenic characterization in vitro was performed by means of Western blotting, and the fractions that reacted with the positive individuals' sera were those of approximate molecular weights of 67 kDa (95%); 20 kDa (55%); 94 kDa (36%); 34 and 36 kDa (23%); 43 and 48 kDa (14%); 16 kDa (9%) and 54kDa (5%). It was concluded that the crude allergenic extract, obtained with Coca liquid from the 16th day growth of Metarhizium anisopliae, contains allergenic fractions and can be used in diagnostic screening tests. © 2005 Esmon Publicidad.
Keywords: Allergen; Balb/c mice; Extracts; Metarhizium anisopliae